(untitled) (Bangladesh Journal of Agricultural Research, 2011)
This study was carried out with 27 bread wheat genotypes during two crop seasons. The great variations were determined between first and second year means of genotypes for all characters. The correlation between grain yield and rate of water losses at heading stage, number of stomata and days to flowering in the first year were found significant and negative. The correlation only between grain yield and days to maturity was positive and significant in the second year. The highest direct positive effects on grain yield were computed for plant height in two years. Although rate of water losses at heading stage showed negative direct effect on grain yield in the first year, it influenced the grain yield positively in the second year. It can be concluded that plant height, days to flowering, maturity, and rate of water losses at heading stage might be effective selection criteria for drought tolerance in semi-arid regions, such as Tekirdag. Keywords: Bread wheat; flag leaf area; rate of water loss; glaucousness; stomata; grain yield. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9257 BJAR 2011; 36(2): 291-303